Course of Preexisting Migraine Following Spontaneous Subarachnoid Hemorrhage - Valdueza, José Manuel; Dreier, Jens Peter; Woitzik, Johannes; Dohmen, Christian; Sakowitz, Oliver; Platz, Johannes; Leistner-Glaess, Stefanie; Witt, Victoria Dorothea (Frontiers in Neurology, 2022)
Background: Our objective was to observe the course of pre-existing migraine following subarachnoid hemorrhage (SAH) in patients with and without craniotomy. Methods: We designed an exploratory analysis and hypothesis-generating study of prospectively collected data starting by recruiting patients suffering from SAH with a Hunt & Hess ≤ 4. Out of 994 cases, we identified 46 patients with pre-existing migraine. According to the treatment we subdivided two groups: first, patients with surgical aneurysm clipping with transection of the middle meningeal artery (MMA) and accompanying trigeminal nerve branches, second, patients with endovascular aneurysm coiling or without any interventional treatment. During follow-up, we recorded the course of migraine frequency, duration, intensity, and character. Results: For both groups (craniotomy n=31, without craniotomy n=15) a significant improvement regarding the preexisting migraine during a mean follow-up of 46 months was seen (p<0.001 and p=0.01). Comparing groups this effect was significantly more pronounced in craniotomy patients (for no recurrence of migraine: p=0.049). After craniotomy, 77.4% patients had no further attacks of migraine headache and 19.4% showed a reduction of >50% while only 2.2% did not report any relevant change. In the nob-surgical group, 46.7% had no further migraine attacks, 20% had a reduction >50% while in 33.3% no change was noted. Conclusions: Our study provides evidence that the dura mater might be related in migraine headache and that transection of the MMA and accompanying trigeminal dural nerve branches might disrupt the pathway leading to a reduction of migraine attacks. However, coiling alone ameliorated migraine complaints.